2018
DOI: 10.5812/ijp.68869
|View full text |Cite
|
Sign up to set email alerts
|

Vertebral Canal Invasion of Cervical Lipoblastoma in Childhood: A Case Report

Abstract: Introduction: Lipoblastoma is a benign tumor that originates in the embryonal fat. This tumor can arise from various anatomical sites such as the extremities, trunk, and neck, but it rarely invades the spinal canal. Case Presentation: We describe a 3-year-old girl with a dumbbell-shaped lipoblastoma that extended into the cervical spine. Although she had no neurological deficit, we performed semi-total resection for decompression to the cord and avoid torticollis. Although a residual tumor was present, she rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…However, little has been mentioned about lipoblastomas developing in the spinal canal. Takebayashi et al [12] reported a 3-year-old girl with a dumbbell-shaped lipoblastoma extending into the cervical spine and recommended early surgical intervention to avoid neurological deficits. Spinal dumbbell lipoblastomas occurring in the epidural space of the entire spinal canal have been reported, resulting in paresis due to compression of the thecal sac [13, 14].…”
Section: Discussionmentioning
confidence: 99%
“…However, little has been mentioned about lipoblastomas developing in the spinal canal. Takebayashi et al [12] reported a 3-year-old girl with a dumbbell-shaped lipoblastoma extending into the cervical spine and recommended early surgical intervention to avoid neurological deficits. Spinal dumbbell lipoblastomas occurring in the epidural space of the entire spinal canal have been reported, resulting in paresis due to compression of the thecal sac [13, 14].…”
Section: Discussionmentioning
confidence: 99%